2002
DOI: 10.1096/fj.01-0899fje
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐proteasome system is responsible for the protection of yeast and human cells against methylmercury

Abstract: The mechanism responsible for the toxic effects of methylmercury (MeHg), an important environmental pollutant, is poorly understood. We have identified a gene, CDC34, that confers resistance to MeHg in Saccharomyces cerevisiae by screening a yeast genomic DNA library. CDC34 encodes a ubiquitin-conjugating enzyme, Cdc34, which is involved in ubiquitin-dependent proteolysis. Overexpression of Cdc34 results in significant resistance to MeHg both in yeast and human cells, and it increases the cellular level of ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…MeHg-induced changes in cellular Ca 2ϩ have been shown to be important (4)(5)(6)(7), as has oxidative stress (4), and glutamate metabolism (8). In both yeast and human cells, overexpression of the ubiquitin-targeting enzyme Cdc34 confers protection against the cytotoxic effects of MeHg, which leads to the suggestion that an unknown protein containing a signal for ubiquitination by Cdc34 is involved in the development of the cytotoxic effects of MeHg (9)(10)(11).…”
Section: T Oxic Organic Mercury Compounds Worry Many Communitiesmentioning
confidence: 99%
“…MeHg-induced changes in cellular Ca 2ϩ have been shown to be important (4)(5)(6)(7), as has oxidative stress (4), and glutamate metabolism (8). In both yeast and human cells, overexpression of the ubiquitin-targeting enzyme Cdc34 confers protection against the cytotoxic effects of MeHg, which leads to the suggestion that an unknown protein containing a signal for ubiquitination by Cdc34 is involved in the development of the cytotoxic effects of MeHg (9)(10)(11).…”
Section: T Oxic Organic Mercury Compounds Worry Many Communitiesmentioning
confidence: 99%
“…However, under in-vivo conditions toxic effects of MeHg may be counterbalanced by a proteasome-mediated protection. Hwang et al (2002) and Hwang (2011) demonstrated in yeast and human cell lines that enhanced resistance is mediated through enhanced expression of Cdc34 or Rad23 proteins which are important for ubiquitination, and accordingly, proteasomal degradation. Our study indicates that in crustaceans the exposure to inorganic mercury may suppress also in-vivo significantly the intracellular protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon was not recognized in yeast cells that expressed the Cdc34 mutants. 6) These results suggest that the function of Cdc34 as a ubiquitin-conjugating enzyme is essential for resistance to MeHg.…”
Section: Reduction In Mehg Toxicity By Up System-mediated Acceleratiomentioning
confidence: 92%